PERLINDUNGAN PEREMPUAN DAN ANAK MELALUI PEMBERIAN SUMBANGAN JAMBAN DI DESA KENDERAN, KECAMATAN TEGALALANG, KABUPATEN GIANYAR PROVINSI BALI - Anak Agung Ayu Ngurah Tini Rusmini , Gorda,; Ni Wayan, Suryathi, (Fakultas Bahasa Asing, 2024)
The objectives of implementing the construction of latrines for residents including poor households (RTM are providing protection for women, the elderly and children, reducing water and land pollution which has a broad impact on the surrounding community, providing basic sanitation facilities that are suitable for the community, increasing community awareness to care on environmental health, and preventing the spread of disease, especially due to defecation in the river. The method used in this community service is to coordinate with the Kenderan Village Secretary, preparing and calculating the implementation budget for the latrine construction mentioned above, it can be concluded that the Protection of Women and Children through Providing Latrine Donations in Kenderan Village, Tegalalang District, Gianyar Regency, Bali Province is a very urgent matter, and appropriate to provide, considering that Kenderan Village was designated as a Tourist Village, it is very ironic that it is still There are people who do not have proper latrines